2019
DOI: 10.2106/jbjs.18.01147
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical Treatment of Localized-Type Tenosynovial Giant Cell Tumors of Large Joints

Abstract: Background: Localized-type tenosynovial giant cell tumor (TGCT) is a rare, neoplastic disease with only limited data supporting treatment protocols. We describe treatment protocols and evaluate their oncological outcome, complications, and functional results in a large multicenter cohort of patients. A secondary study aim was to identify factors associated with local recurrence after surgical treatment.Methods: Patients with histologically proven localized TGCT of a large joint were included if they had been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 33 publications
(37 reference statements)
1
12
0
5
Order By: Relevance
“…Contamination of the joint in intralesional resections is rarely reported, but a large multicenter study of N-TGCT showed a lower LRR after open versus arthroscopic surgery (13 % versus 20 %). [47] In the posterior compartment, open resection is preferred [IV, B].…”
Section: N-tgctmentioning
confidence: 99%
“…Contamination of the joint in intralesional resections is rarely reported, but a large multicenter study of N-TGCT showed a lower LRR after open versus arthroscopic surgery (13 % versus 20 %). [47] In the posterior compartment, open resection is preferred [IV, B].…”
Section: N-tgctmentioning
confidence: 99%
“…lokalizirani TGCT ( u daljnjem tekstu LTGCT) ili zahvaćati čitav zglob, tzv. difuzni TGCT, pri čemu je histološka slika kod oba oblika jednaka (1)(2)(3)(4). Točna etiologija bolesti je nepoznata.…”
Section: Uvodunclassified
“…Točna etiologija bolesti je nepoznata. No, zbog prisutnosti kromosomske translokacije t(1;2) (CSF-1;COL6A3) u mononuklearnim stanicama, moguće je i klonalno neoplastično podrijetlo (2)(3)(4). Stopa pojavnosti TGCT-a u ukupnoj populaciji iznosi deset slučajeva na milijun ljudi za lokalizirani, odnosno četiri slučaja na milijun ljudi za difuzni oblik bolesti (2).…”
Section: Uvodunclassified
See 1 more Smart Citation
“…However, TGCT has shown a propensity for local recurrence after surgical resection, especially diffuse TGCT, with a local recurrence rate of up to 10–48% in previous studies ( 4 8 ). Therefore, gross total resection (GTR) with postoperative radiotherapy has been recommended for TGCT to reduce local recurrence ( 9 ). Due to the special anatomy and functions of the spine, the clinical characteristics, treatment method, and prognosis of spinal TGCT might be different from those of TGCT of the extremities.…”
Section: Introductionmentioning
confidence: 99%